Carbon nitride/positive carbon black anchoring PtNPs assembled by γ-rays as ORR catalyst with excellent stability. (31st May 2021) - Liu, Liangsen; Shi, Xiang; Wang, Wei; Pei, Mengfan; Hong, Chunxia; Xue, Yanling; Xu, Zhiwei; Tian, Feng; Guo, Xingfeng
Abstract: Electrocatalytic performance of low-cost graphitic carbon nitride (CN) is greatly limited by its limited conductivity and small specific surface area. Herein, a simple and cost-effective idea to produce novel nanocomposite is constructed by the CN and cetyl trimethyl ammonium bromide functionalized carbon black (CB) anchored platinum nanoparticles as highly efficient oxygen reduction catalysts based on gamma irradiation. The assembled carbon nitride/positive carbon black anchoring PtNPs (Pt/CN2 -CB + 1 ) catalyst exhibits significantly improved specific surface area, high graphitization, and uniformly dispersed ultra-small platinum nanoparticles. For the oxygen reduction reaction (ORR) performance, the catalyst shows more positive onset-potential (0.93 V versus RHE) and larger diffusion limiting current density (5.65 mA cm −2 ) compared with benchmark Pt/C catalysts in alkaline medium. Moreover, the Pt/CN2 -CB + 1 catalyst exhibits a small Tafel slope (92 mV dec −1 ). Besides, the catalyst was demonstrated the remarkable methanol tolerance and good long-term stability under working conditions. This work provides a new and effective γ -rays irradiation for synthesizing the carbon nitride catalysts for energy conversion and storage applications.